2012
DOI: 10.2478/v10266-012-0125-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Cast Irons Solidification With Various Types of Graphite

Abstract: The contribution summarises the results of oxygen activity determinations, which were measured and registered continuously in castings from cast irons with various types of graphite. The results were used to find the relationship between two variables: natural logarithm of oxygen activities and reverse value of thermodynamic temperature 1 /T. Obtained regression lines were used to calculate oxygen activity at different temperatures, to calculate Gibbs free energy ΔG at the different temperatures and to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Elbel et. al [14] also recorded the oxygen activity for FG, CG and SG at 1350 °C which are 0.97 ppm, 0.30 ppm and 0.16 ppm respectively.…”
Section: Introductionmentioning
confidence: 95%
“…Elbel et. al [14] also recorded the oxygen activity for FG, CG and SG at 1350 °C which are 0.97 ppm, 0.30 ppm and 0.16 ppm respectively.…”
Section: Introductionmentioning
confidence: 95%
“…9 Another research was conducted by Elbel and Hampl and concluded that titanium content higher than 0?1% greatly enlarged the danger of pinhole occurrence. 10 Svensson et al conducted a series of effects of alloying elements on CGI and found that Cu and Sn do not influence the vermicular ratio while they strongly promote the pearlite and therefore the mechanical properties. [11][12][13] However, Sn was demonstrated by Shaban and his colleagues to increase the percentage of compacted graphite and graphite aspect ratio, which is disobedient to the results of Svensson.…”
Section: Introductionmentioning
confidence: 99%